Hippocampal modulation of auditory processing in epilepsy. Issue 1 (6th December 2020) - Shigeto, Hiroshi
Abstract: The hippocampus is anatomically and functionally connected to other brain regions　tightly. Especially in the field of memory research, it has become clear that the connections between the cerebral cortex, thalamus, and hippocampus are regulated via slow‐wave rhythms and high‐frequency oscillation. In addition, the hippocampus, as a limbic system, is more excitable to inputs than the cerebral cortex and has a reverberant circuit structure, which induces long‐lasting neural activity. Because of such characteristics of the hippocampus, it is treated as a key structure in epilepsy. Auditory processing has been shown to be affected by hippocampal activity, and impaired auditory processing function in patients with medial temporal lobe epilepsy has been elucidated using techniques such as cognitive behavior tests and electrophysiological recordings. We recorded the auditory‐induced magnetoencephalography of patients with refractory medial temporal lobe epilepsy and examined which hemisphere was more affected. In contrast to previous language studies, we only used simple tone stimulation, by which we could obtain the laterality information regarding epileptic activity and left‐right difference. In this article, we reviewed the effects of hippocampal activity on brain function, including the findings of our auditory stimulus‐induced magnetic field recordings of medial temporal lobe epilepsy.